Knowledge and perception regarding effectiveness in influenza vaccines among General Practitioners in Germany: A national survey. (December 2022) - Hadigal, Sanjay; Cook, Joseph
Highlights: The terms vaccine efficacy and vaccine effectiveness are not interchangeable. Vaccine effectiveness happens in the real world, and efficacy in clinal trials. However, 41% of physicians said that the terms can be used interchangeably. Knowledge of the difference in terms can help support well-informed decisions. Getting the annual flu shot is more important than the type of flu vaccine. Abstract: Objectives: To understand physicians' knowledge and perception regarding the effectiveness of influenza vaccines and to communicate the importance of understanding the differences in terms of vaccine efficacy and vaccine effectiveness. Methodology: This cross-sectional quantitative online survey was conducted using a questionnaire comprising 20 questions, between September 11 and 19, 2021. The survey was conducted across 14 cities in Germany, including physicians actively involved in influenza vaccine purchasing decisions. Descriptive statistics were used to summarize the data and paired t -test was performed to compare the physicians' understanding of efficacy and effectiveness. Results: Eighty physicians (21%) completed the survey. Physicians defined the terms vaccine efficacy and effectiveness similarly, with only minimal distinctions. Forty-one percent agreed that both terms can be used interchangeably in clinical practice. A higher proportion used the phrase "observational study" for vaccine efficacy and 21% associated "controlled environment" with effectiveness. The majority of physicians indicated that antigen match to circulating strain plays a large role in overall effectiveness and vaccine coverage strongly influences overall influenza case prevention. Vaccine performance in observational studies under so-called "real-world conditions" and (vaccine independent) strain match were the most important factors to assess vaccine performance and vaccine choice. Conclusion: These findings show that physicians in Germany use the terms vaccine efficacy and vaccine effectiveness interchangeably. A better knowledge of the differences between these terms will help to make informed decisions on the choice of influenza vaccine for its population. Finally, and most important, increasing the annual flu vaccine uptake rates will have more and the greatest beneficial impact on reducing flu-related disease and public health, regardless of the expression of the benefits for different vaccine types.